Muscle function and homeostasis require cytokine inhibition of AKT activity in Drosophila - Katrin Kierdorf; Fabian Hersperger; Jessica Sharrock; Crystal M Vincent; Pinar Ustaoglu; Jiawen Dou; Attila Gyoergy; Olaf Groß; Daria E Siekhaus; Marc S Dionne (eLife, 2020)
Unpaired ligands are secreted signals that act via a GP130-like receptor, domeless, to activate JAK/STAT signalling in Drosophila. Like many mammalian cytokines, unpaireds can be activated by infection and other stresses and can promote insulin resistance in target tissues. However, the importance of this effect in non-inflammatory physiology is unknown. Here, we identify a requirement for unpaired-JAK signalling as a metabolic regulator in healthy adult Drosophila muscle. Adult muscles show basal JAK-STAT signalling activity in the absence of any immune challenge. Plasmatocytes (Drosophila macrophages) are an important source of this tonic signal. Loss of the dome receptor on adult muscles significantly reduces lifespan and causes local and systemic metabolic pathology. These pathologies result from hyperactivation of AKT and consequent deregulation of metabolism. Thus, we identify a cytokine signal that must be received in muscle to control AKT activity and metabolic homeostasis.